Evaluation of The Computer Laboratory During The Covid-19 Pandemic at SMK Negeri 7 Baleendah - Nareswari, Puspita Alfira; Permana, Asep Yudi; Dewi, Nitih Indra Komala (Journal of Architectural Research and Education, 2021)
Abstract - This study aims to obtain a general description of the condition and fulfillment of the facilities and infrastructure of the computer laboratory for the Modeling and Building Information Design (DPIB) program at SMK Negeri 7 Baleendah based on the standards of the Minister of Education and Culture No. 34 of 2018. The purpose of this study is also to assess the compliance of health protocol facilities at SMK Negeri 7 Baleendah and to obtain a computer laboratory layout plan that is in accordance with health protocol rules during the Covid-19 pandemic. This research is an evaluation research. Data collection techniques in this study by means of observation and documentation. The results of this study indicate the level of achievement of facilities and infrastructure at SMK Negeri 7 Baleendah based on the standards of Permendikbud No. 34 of 2018 reached 83% in computer laboratory room infrastructure, the achievement was included in the very feasible criteria and in the facilities it reached 72.91% including the feasible criteria. The results of the evaluation on health protocol facilities based on existing standards, the availability of disinfectant liquid has not been met, the sink near the computer laboratory room is not available for hand washing soap, and the layout of the computer laboratory room has not been given a distance of 1.5 meters. Design recommendations for the DPIB program computer laboratory room at SMK Negeri 7 Baleendah by changing the type of opening, the position of the sink placed next to the entrance to the computer laboratory room and the layout of the room spaced 1.5 meters apart from each seat. The results of the evaluation on health protocol facilities based on existing standards, the availability of disinfectant liquid has not been met, the sink near the computer laboratory room is not available for hand washing soap, and the layout of the computer laboratory room has not been given a distance of 1.5 meters. Design recommendations for the DPIB program computer laboratory room at SMK Negeri 7 Baleendah by changing the type of opening, the position of the sink placed next to the entrance to the computer laboratory room and the layout of the room spaced 1.5 meters apart from each seat. The results of the evaluation on health protocol facilities based on existing standards, the availability of disinfectant liquid has not been met, the sink near the computer laboratory room is not available for hand washing soap, and the layout of the computer laboratory room has not been given a distance of 1.5 meters. Design recommendations for the DPIB program computer laboratory room at SMK Negeri 7 Baleendah by changing the type of opening, the position of the sink placed next to the entrance to the computer laboratory room and the layout of the room spaced 1.5 meters apart from each seat.Keywords - Computer Laboratory, Facilities and Infrastructure, Health protocol, Standard of Computer Laboratory Facilities and Infrastructure for SMK.